Established, new and future disease modifying therapies for MS. Issue 5 (September 2015) - Binks, S; Dobson, R
<x xml:space="preserve">Abstract</x> Over recent years the pace of therapeutic development in multiple sclerosis has increased, and there are now 10 disease‐modifying therapies available. In this review the authors discuss the evidence supporting the use of these drugs and consider which new treatments may be available in the future.